Circadian variation in fibrinolytic activity in patients with variant angina. Issue 2 (February 1994) - Masuda, T.; Ogawa, H.; Miyao, Y.; Yu, Q.; Misumi, I.; Sakamoto, T.; Okubo, H.; Okumura, K.; Yasue, H.
Abstract : BACKGROUND--Coronary artery spasm induces activation of the coagulation system. Turnover and maintenance of thrombus depend not only on formation but also on lysis. The relation between coronary spasm and fibrinolytic system has not been elucidated. OBJECTIVE--To examine whether there is impairment of or a circadian variation in fibrinolytic activity in patients with variant angina. METHODS--Plasminogen activator inhibitor (PAI) activity and concentrations of tissue plasminogen activator (t-PA) antigen were measured in venous plasma samples taken at 2200, 0600, and 1400 and 24 h Holter tapes were recorded in 15 patients with variant angina, 12 patients with stable exertional angina, and 12 controls. RESULTS--There were significant circadian variations in PAI activity and t-PA antigen with peak values at 0600 in all three groups. Mean (SEM) PAI activity (IU/ml) at 2200, 0600, and 1400 was 6.1 (1.1), 11.0 (1.3), and 4.4 (0.6) in the variant angina group; 1.8 (0.7), 5.6 (1.1), and 1.2 (0.3) in the stable exertional angina group; and 1.1 (0.5), 4.5 (0.8), and 0.7 (0.3) in the control group. Furthermore, both plasma PAI activity and t-PA antigen concentrations were significantly higher in the variant angina group than in the stable exertional angina group and the control group at each sampling time. CONCLUSIONS--In patients with variant angina there was a circadian variation in fibrinolytic activity, which was lowest in the early morning, and impaired fibrinolytic activity particularly in the early morning, when attacks of angina occur most frequently.